Isolation and Screening of Endophytic Microbes from Morinda citrifolia and their Ability to Produce Anti-Microbial Substances - SHIRLY KUMALA; ENDRO BUDI SISWANTO (Microbiology Indonesia, 2007)
Assaying for, and isolation and screening of endophytic microbes from the Morinda citrifolia plant and their ability to produce anti-microbial substances was carried out. Endophytic microbes are microorganisms that live asymptomatically within the living tissue of host plants. Microorganisms such as bacteria, fungi, and yeast can be associated with the host and produce secondary metabolites. These secondary metabolites may be enzymes and other bioactive substances with medicinal activity such as anti-arthritic, anti-cancer, and anti-microbial compounds. The aims of these experiments was to investigate the ability of endophytic microbes isolated from M. citrifolia to produce secondary metabolites which can act as anti-microbial agents. A direct seed inoculating technique was used by planting the plant sample onto the surface of Nutrient Agar and Potato-Dextrose Agar. Assessment of their ability to produce anti-microbial substances was conducted by growing the endophyte isolates in Muller Hinton Broth for bacterial isolates, and in Potato-Dextrose Yeast Broth for fungal isolates. The agar diffusion method using paper disk was applied to assay the anti-microbial activity of each substance. The results of the endophyte isolation in these experiments gave five bacterial isolates and eleven fungal isolates. All of the bacterial isolates showed a broad antimicrobial spectrum while ten of the fungal isolate demonstrated broad anti-microbial activity and four out of the ten fungal isolates had activity towards Candida albicans.